Characterisation of carotenoid content in diverse local sweet potato (ipomoea batatas) flesh tubers - Kammona, Suhair; Othman, Rashidi; Jaswir, Irwandi; Jamal, Parveen (2015)
Sweet potato (Ipomoea batatas) is one of the most important food crops in the world. Sweet potato is rich with carotenoids and pro-vitamin A. Carotenoids compounds are commonly found in fruits and vegetables and are responsible for yellow, orange, and red pigmentations. Carotenoids are antioxidants compounds with pharmaceutical and medicinal benefits. Carotenoids such as α-carotene and β-carotene react as provitamin A in the human body, while lutein and zeaxanthin are two major components of the macular pigment of the retina.